2005
DOI: 10.1197/j.aem.2004.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Terrorist Bombings of the Neve Shalom and Beth Israel Synagogues on a Hospital in Istanbul, Turkey

Abstract: Objectives: The authors sought to estimate the impact of the open-air mass-casualty terrorist bombings of the Neve Shalom and Beth Israel Synagogues in Istanbul, Turkey, on November 15, 2003, on the American Hospital (AH) in terms of resource utilization, epidemiologic outcomes, and time course of emergency needs. Methods: A retrospective descriptive study using data from hospital records of injured survivors who used the emergency department at AH on November 15, 2003, to determine the number and percentage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Victims who are not breathing at the site, who have 100% body burns, or who have fixed and dilated pupils, do not survive, and resuscitation is discouraged. The walking wounded will take themselves for attention, and this is where the secondary triage assures that the most severely wounded, who usually arrive later from the scene, receive the more critical immediate hospital attention before those who arrive injured, but awake and ambulatory [2,5,7,9,10,[24][25][26].…”
Section: Treatment and Management Strategiesmentioning
confidence: 99%
“…Victims who are not breathing at the site, who have 100% body burns, or who have fixed and dilated pupils, do not survive, and resuscitation is discouraged. The walking wounded will take themselves for attention, and this is where the secondary triage assures that the most severely wounded, who usually arrive later from the scene, receive the more critical immediate hospital attention before those who arrive injured, but awake and ambulatory [2,5,7,9,10,[24][25][26].…”
Section: Treatment and Management Strategiesmentioning
confidence: 99%
“…A characteristic injury pattern of bomb explosions is one of a complex but often non-lethal nature, where most casualties do not require hospitalization as only a small number have severe injuries [9,32,39,55,62,75,82,90,[93][94][95][96]. The vast majority of deaths from bombings usually take place at the scene or en route to the hospital, followed by few early and occasional late deaths [17,58,62,97]. In a study of 33 MCAs, Einav and colleagues [96] found that roughly a fifth (n = 236; 20.4%) of the injured were considered urgent casualties.…”
Section: Encountering Uncommon Injuriesmentioning
confidence: 99%
“…In a study of 33 MCAs, Einav and colleagues [96] found that roughly a fifth (n = 236; 20.4%) of the injured were considered urgent casualties. Consequently, a large majority of surviving victims can likely be triaged and treated on an outpatient basis [17,97]. Medical preparedness should anticipate most injuries from bombings to be nonfatal secondary and tertiary blast injuries [9,10,44,81,97].…”
Section: Encountering Uncommon Injuriesmentioning
confidence: 99%
See 2 more Smart Citations